(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
Nanosized hydroxyapatite with silicon substitution Ca10(PO4)6âˆ’x(SiO4)x(OH)2âˆ’xâ–¡x (0 â‰¤ x â‰¤ 2)Â of same silicon concentrations, variation of pH and the method of inverse and direct synthesis were successfully prepared first time by the theoretical maximumÂ of incorporation of Si into the hexagonal apatite structureÂ Â byÂ Â precipitation method aqueous. The effects Â Â Â Â Â Â Â of the Si substitution on crystallite size, particle size and morphology of the powders were investigated. The crystalline phase, microstructure, morphology and particle size of hydroxyapatite and silicon substituted hydroxyapatites were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), EDX coupled with SEM and transmission electron microscopy (TEM). The samples were successfully synthesized as a single-phase apatite, and crystallization of apatite was enhanced during heating. The results obtained in this study show that the kinetics between different direct and inverse process showed different reactivities, in the presence of varying pH. Compared with the two methods, the inverse method have higher kinetic in the formation of hydroxyapatite silicate because of the difference in lattice parameters. The grain size of Si-HA samples is clearly finer than that of pure HA sample and this decreases with increasing Si content. The growth of HA nanorods with temperature can be described by â€œoriented attachmentâ€. According to this theory the adjacent HA crystallites would coalesce in one particular direction on the (1 1 0) high energy planes, creating templates Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â to form elongated rod-like structure.Â Fourier Transform Infrared Spectroscopy analysis reveals, Â the silicon incorporation to hydroxyapatite lattice occurs via substitution of silicate groups for phosphate groups. Substitution of phosphate groupÂ Â Â by silicate in the apatite structure results in a increase in the lattice parameters in both a-axis and c-axis of the unit cell.